The Global Chilling Effects of Antidumping Proliferation - Hylke Vandenbussche; Maurizio Zanardi (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2006)
Advocates of antidumping (AD) laws downplay their effects by arguing that the trade flows that are subject to AD are small and their distortions negligible. This paper is the first to counter that notion by quantifying the worldwide effect of AD laws on aggregate trade flows. The recent proliferation of AD laws across countries provides us with a natural experiment to estimate the trade effects of adopting versus using AD laws; differences in the intensity of use among countries with older AD laws allow us to investigate reputation effects. For this purpose, we estimate worldwide trade flows using a gravity equation spanning 21 years (1980-2000) of annual observations. Our estimates confirm that AD effects are not small. Among other findings, new tough users have their aggregate imports depressed by 15.7 billion US a year (or 6.7%) as a result of the AD measures they have imposed. For a traditional user like the United States, current AD measures depress annual imports by almost 20 billion US on top of the cumulative negative effect of reputation. For some countries, the dampening effects of AD laws on trade flows are found to nearly offset the gains from trade liberalization.
Keywords: F13; F14; 330; Antidumping; gravity equation; trade liberalization; trade flows; Antidumping; Außenhandelseffekt; Außenhandelsliberalisierung; Gravitationsmodell; Schätzung